Androgen withdrawal fails to induce detectable tissue hypoxia in the rat prostate. Issue 8 (27th March 2014) - Regter, Sietze; Hedayati, Mohammad; Zhang, Yonggang; Zhou, Haoming; Dalrymple, Susan; Koch, Cameron J.; Isaacs, John T.; DeWeese, Theodore L.
<x xml:space="preserve">Abstract</x> BACKGROUND It has been reported that significant hypoxia may occur in the rat prostate following androgen deprivation (AD). It is well known that hypoxia substantially reduces radiation sensitivity of cells both in vitro and in vivo. Given that contemporary management of men with intermediate and high‐risk prostate cancer includes the use of neoadjuvant androgen suppression and radiation, AD‐induced hypoxia in the prostate could result in suboptimal therapeutic results. Given this concern, we fully investigate possible AD‐induced hypoxia in the ventral prostate (VP) of adult rats by two independent methods. METHODS Tissue pO2 levels in the VP of adult Spraque‐Dawley rats were evaluated prior to and at various time points following castration by two independent techniques. First, an Oxylab tissue oxygen monitor with a 240 μm probe was used for quantitative monitoring of global VP oxygenation. Second, fluorescence immunohistochemistry using the hypoxia marker EF5, known to be metabolically activated by hypoxic cells, was used to evaluate cell‐to‐cell variation in hypoxia at various days post‐castration. RESULTS Neither the oxygen probe nor EF5 method demonstrate any substantive change in pO2 levels in the rat VP at any time point post‐castration. CONCLUSIONS We find no evidence that the rat VP becomes hypoxic at any point following castration using an animal model that closely mimics the human prostate. These data are in contrast to previous reports suggesting prostatic hypoxia occurs following AD and provide assurance that our present therapeutic strategy of neoadjuvant AD followed by radiation is not compromised by AD‐induced tissue hypoxia. Prostate 74:805–810, 2014. © 2014 Wiley Periodicals, Inc.